DJ-1 Inhibits α-Synuclein Aggregation by Regulating Chaperone-Mediated Autophagy - Xu, Chuan-Ying; Kang, Wen-Yan; Chen, Yi-Meng; Jiang, Tian-Fang; Zhang, Jia; Zhang, Li-Na; Ding, Jian-Qing; Liu, Jun; Chen, Sheng-Di (Frontiers in Aging Neuroscience, 2017)
α-Synuclein misfolding and aggregation play an important role in the pathogenesis of Parkinson’s disease (PD). Loss of function and mutation of the PARK7/DJ-1 gene cause early-onset familial PD. DJ-1 can inhibit α-synuclein aggregation, and may function at an early step in the aggregation process. Soluble wild-type α-synuclein is mainly degraded by chaperone-mediated autophagy (CMA), and impairment of CMA is closely related to the pathogenesis of PD. Here, we investigated whether DJ-1 could reduce α-synuclein accumulation and aggregation by CMA. DJ-1 knockout mice and DJ-1 siRNA knockdown SH-SY5Y cells were used to investigate the potential mechanisms underlying the relationship between DJ-1 deficiency and α-synuclein aggregation. First, we confirmed that DJ-1 deficiency increased the accumulation and aggregation of α-synuclein in both SH-SY5Y cells and PD animal models, and overexpression of DJ-1 in vitro effectively decreased α-synuclein levels. α-Synuclein overexpression activated CMA by elevating the levels of lysosome-associated membrane protein type-2A (LAMP2A), but DJ-1 deficiency suppressed upregulation of LAMP2A. DJ-1 deficiency downregulated the level of lysosomal 70 kDa heat-shock cognate protein but not the levels of that in homogenates. Further studies showed that DJ-1 deficiency accelerated the degradation of LAMP2A in lysosomes, leading to the aggregation of α-synuclein. Our study suggests that DJ-1 deficiency aggravates α-synuclein aggregation by inhibiting the activation of CMA and provides further evidence of the molecular interaction between PD-related proteins via the CMA pathway.